Nutritional Status of School-Going Adolescents in Eastern Part of Nepal - Kafle, Tika Kumari; Kafle, Tara Kumari; Hawlader, Md. Delwer Hossain; Rimal, Hem Sagar; Sapkota, Durga (Birat Journal of Health Sciences, 2020)
Introduction: Nutrition is one of the key factors that affects every sphere of human health. Its effect on physical and cognitive development is vital for performance and productivity especially among the children and adolescents. Hemoglobin and body mass index (BMI) are key factors to assess the nutritional status among adolescents. Objectives: This study aims to examine the nutritional status and its associated factors among school-going adolescents Methodology: Descriptive cross-sectional study design was adopted with sample size 810 involving 11 to 17 years’ school going adolescents in Eastern Development Region of Nepal. Multistage probability sampling technique was used to draw the sample and pre-designed structured questionnaire and standard measurement tools were used to assess the nutritional status. Ethical approval and written informed consent were taken from concerned authorities. Data were entered in EPI Data and analyzed by SPSS. Chi-square test was used to find association. Results: Among 810 adolescents, 52.5 % were females and 47.5 % were males. The mean age of participants was 14.5 years. Mean hemoglobin and BMI were measured 11.13 mg/dl with SD 1.57 and 18.87 with SD 2.79 respectively. Variation measured significant by sex, ethnicity, parents’ education, family type and ecological belts for BMI (p<.05). Similarly, age, sex, ethnicity, property index, parents’ education and occupation were significantly associated with hemoglobin (p<.05). Conclusion: The low BMI as well asanemia were widely prevalent among school-going adolescents in Eastern part of Nepal. The females had better BMI than males but males were less anemic than females.